Probing the compositional and rheological properties of gastropod locomotive mucus - Barajas-Ledesma, Edgar; Holland, Chris (Frontiers in Soft Matter, 2023)
Gastropods, such as snails and slugs, can excrete mucus to aid in movement and adhesion. However, very few studies have examined the physical relationship between mucus composition and function. Here, we explore the role of mucus polymers (specifically their proteins) and their influence on the material properties of locomotive mucus. Using a range of spectroscopic, thermal, and rheological analytical tools, we characterised locomotive mucus from six gastropod species across four families. We report that all mucus tested consisted of 97%–99% water, and the remaining 1%–3% solid content contained a range of proteins (41–377 kDa, 18 of which are previously undocumented), which we propose contribute to its weak gel behaviour (1.58–36.33 Pa•s at 1 rad/s). Our results indicate that mucus properties are also grouped at the family level, suggesting that niche-specific adaptation occurs in these materials. We expect our study to offer a broader approach to how a correlation between properties is crucial for understanding the stability and functionality of snail mucus.